Dietary β‐glucan modulate haematological parameters, cytokines and gene expression in TLR and ERK pathways of rainbow trout (Oncorhynchus mykiss) during infection by Aeromonas salmonicida. (13th December 2019) - Ji, Liqin; Fu, Songzhe; Sun, Guoxiang; Li, Xian; Liu, Ying
Abstract: To explore the role of β‐glucan (0, 0.05%, 0.1% and 0.2%) in resisting bacteria, rainbow trout ( Oncorhynchus mykiss ) was challenged with Aeromonas salmonicida after 42‐day β‐glucan administration, and then sampled at 0, 2, 4 and 6 days post infection (dpi). The data showed that 0.2% β‐glucan reduced the accumulated mortality rates compared with the ICG (infected control group) ( p < .05 ). The white blood cells, red blood cells and haemoglobin were higher in the 0.2% β‐glucan group (BG) than the ICG ( p < .05 ). 0.1% and 0.2% β‐glucan elevated serum total antioxidative capability and glutathione activity but alleviated the increase of serum alkaline phosphatase activity and glucose concentration ( p  < .05) during infection. Serum TNF‐α, IL‐1β, IL‐8 and IgM in three BGs elevated remarkably on 6 dpi compared with the ICG ( p < .05 ). Expression of tnf, il1b and cxcl8 of the head kidney in the 0.1% and 0.2% BGs was higher than the ICG on 4 dpi while ighm expression in the 0.2% BG was higher than in the ICG on 2 and 6 dpi ( p < .05 ). 0.1% and 0.2% β‐glucan increased the expression of tlr5m, tlr5s, tmek and myd88 in the spleen after infection ( p  < .05). Similarly, 0.2% β‐glucan up‐regulated the expression of tmek, myd88, oncmyk‐dab and c3 in head kidney ( p  < .05). Overall, 0.2% dietary β‐glucan effectively decreased accumulated mortality rate by modulating the biochemistry process, cytokines, and activating TLR and ERK signalling pathways during A. salmonicida infection.